RAPD MARKER-BASED GENETIC DIVERSITY AMONG RELEASED FINGER MILLET (ELEUSINE CORACANA. GAERTN.) CULTIVARS WITH KNOWN PEDIGREE - S. RAMESH; H. R. SOWMYA; A. MOHAN RAO; S. BARATHI; JAYARAME GOWDA (The Bioscan, 2015)
The validity of concern regarding the narrow genetic base of released finger millet cultivars was explored. Randomly Amplified Polymorphic DNA (RAPD) marker-based assay of 35 finger millet cultivars with known pedigree indicated substantial inter-cultivar genetic distance ranging from 0.90 to 0.26. While the cultivars, MR 2 and HR 911 were highly similar, Indaf 9 and OEB 57 were highly divergent at RAPD loci. The cultivars could be grouped into nine clusters based on their genetic distance. The cultivars within a cluster had similar parentage and those grouped into different clusters had diverse parental origin. The preliminary evidences from the study did not completely support the hypothesis of narrow genetic base of finger millet cultivars developed and released for commercial cultivation in India.